Developing learning methods of Indonesian as a foreign language - Suparsa, I Nyoman; Mantra, Ida Bagus Nyoman; Widiastuti, Ida Ayu Made Sri (International Journal of Social Sciences and Humanities, 2017)
The present study was conducted which aims at developing teaching methods of Indonesian as a foreign language. This study was carried out for two years in the form of Research and Development design to develop accuracy of teaching methods to be employed to teach the Indonesian language. The study was conducted as an important and crucial issue encountered by prospective teachers of Indonesian as a foreign language to face global challenges in which teachers of Indonesian are urgently required to teach effectively. In addition, this study was conducted to prepare the Indonesian teachers to be professional teachers and ready to face the competitive world of work. In the first year, the research was focused on creating a draft of effective learning methods to teach Indonesian as a foreign language. Consequently, this study was started by analyzing the teaching methods that have been used by various language learning institutions. The second year, the study is mainly focused on trying out and validated the learning methods to ensure their effectiveness to teach Indonesian as a foreign language.